Three Gorges Dam Environmental Monitoring Network and Practice - Huang, Zhenli (Springer Berlin Heidelberg, 2018)
This is the first English book talking about the Three Gorges Project Eco-Environmental Monitoring System (TGPEEMS). It presents lessons learned in construction of large dam projects at home and abroad in this field, identifies existing problems before suggesting a scientific improvement plan and, most importantly, it studies modification of the TGPEEMS to adapt it to the changing situation after the impoundment of the reservoir, and provides an essential overview of measures and progress in the ecological and environmental protection for the ongoing project. As such, it offers a valuable reference guide for both researchers and environmental decision-makers.Prof. Zhenli Huang works at the National Research Center for Sustainable Hydropower Research, China Institute of Water Resources and Hydropower Research. Prof. Bingfang Wu works at the Institute of Remote Sensing Applications, Chinese Academy of Sciences, China.